Addressing scale and seasonality in the design of sugarcane to ethylene glycol biorefineries. (20th February 2022) - Valentim Bastos, João Bruno; Soares Santos Maia, Jeiveison Gobério; Borschiver, Suzana; Szklo, Alexandre; Secchi, Argimiro Resende
Abstract: An appropriate techno-economic assessment of biorefineries is essential for consolidating a bio-based economy. Herein, the effects of scale and seasonality on the design of a sugarcane to ethanol biorefinery were assessed using an extensive process simulation and economic modeling methodology. Four sub-processes were simulated for eight different scales: ethanol from sugarcane, ethanol dehydration to ethylene, ethylene to mono ethylene glycol (MEG), and electricity and steam generation from bagasse. Models for capital expenditure and minimum selling price versus product capacity were developed for ethanol, bio-ethylene, and MEG. The integrated biorefinery was analyzed for 200 kt/yr and 440 kt/yr bio-ethylene capacities, considering three regions of Brazil: Northeast, South-central, and São Paulo/Paraná. Seasonality effects were mitigated by establishing a storage park alongside the biorefinery. The results indicated that the selling price of bio-MEG must be at least 20–30% higher than the fossil-based MEG to ensure competition. The 440 kt/yr biorefinery located in the South-central region had the lowest bio-MEG selling price, however, it required an outsized distillery. Moreover, scale and seasonality had a significant impact on the competitiveness of the biorefinery. The bio-MEG selling price might vary by up to 22%, depending on the specific combination of these factors. Graphical abstract: Image 1 Highlights: Impacts of scale and seasonality on sugarcane biorefineries were evaluated. Capital expenditure and minimum selling price models were developed and validated. A 440 kt/yr bio-ethylene plant had the highest economic performance. The optimum scale included ethanol storage parks due to low distillery capacity. The bio-MEG price could vary by 22% based on feedstock seasonality and plant scale.